The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1073/pnas.95.22.13120
|View full text |Cite
|
Sign up to set email alerts
|

An inhibitor of HIV-1 protease modulates proteasome activity, antigen presentation, and T cell responses

Abstract: Inhibitors of the protease of HIV-1 have been used successfully for the treatment of HIV-1-infected patients and AIDS disease. We tested whether these protease inhibitory drugs exerted effects in addition to their antiviral activity. Here, we show in mice infected with lymphocytic choriomeningitis virus and treated with the HIV-1 protease inhibitor ritonavir a marked inhibition of antiviral cytotoxic T lymphocyte (CTL) activity and impaired major histocompatibility complex class I-restricted epitope presentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
180
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 258 publications
(195 citation statements)
references
References 32 publications
13
180
2
Order By: Relevance
“…This immunomodulatory effect was neither due to the inhibition of viral replication nor to a direct effect on CTL activation, but was attributed to a reduction in the presentation of immunodominant LCMV epitopes. Interestingly, Ritonavir was found to inhibit the chymotrypsin-like activity of the 20S proteasome in vitro, while the trypsin-like activity was enhanced (41,42). We reasoned that the modulation of proteasome activity would account for the in vivo reduction of Ag presentation, but we could not exclude that this effect was, at least in part, due to the inhibition of other proteases in APC.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This immunomodulatory effect was neither due to the inhibition of viral replication nor to a direct effect on CTL activation, but was attributed to a reduction in the presentation of immunodominant LCMV epitopes. Interestingly, Ritonavir was found to inhibit the chymotrypsin-like activity of the 20S proteasome in vitro, while the trypsin-like activity was enhanced (41,42). We reasoned that the modulation of proteasome activity would account for the in vivo reduction of Ag presentation, but we could not exclude that this effect was, at least in part, due to the inhibition of other proteases in APC.…”
Section: Discussionmentioning
confidence: 94%
“…Recently, we have found that the treatment of LCMV-infected mice with the HIV-1 protease inhibitor Ritonavir at therapeutic concentrations markedly inhibited the generation and expansion of LCMV-specific CTLs in vivo (42). This immunomodulatory effect was neither due to the inhibition of viral replication nor to a direct effect on CTL activation, but was attributed to a reduction in the presentation of immunodominant LCMV epitopes.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this concept, the direct inhibitory effects of the protease inhibitor ritonavir on CTL function and on antigen presentation, demonstrate that this class of agents directly modulates immune function. 103 Furthermore, several lines of evidence suggest that protease inhibitors may affect T cell turnover in a manner that is independent of changes in viral load. If rebound in CD4 T cell counts are solely related to decreases in viral load, one would predict similar increases in CD4 T cell levels with similar degrees of viral suppression whether this was achieved by protease inhibitor or non-protease inhibitor based therapy.…”
Section: Discussionmentioning
confidence: 99%
“…During chronic infections or cancer, it may be beneficial to alter the spectrum or level of epitopes produced in vivo to boost T cell recognition or to increase the potential targets for T cell recognition. The HIV protease inhibitor ritonavir has been reported to impair proteasome activity (59). It may be interesting to determine whether this compound or other proteasome inhibitors that can be used in vivo alter CTL activity toward epitopes such as NP [147][148][149][150][151][152][153][154][155] in animal models.…”
Section: Discussionmentioning
confidence: 99%